2022
DOI: 10.1017/s1368980022001422
|View full text |Cite
|
Sign up to set email alerts
|

Red meat consumption is associated with prediabetes and diabetes in rural Vietnam: a cross-sectional study

Abstract: Objective: To examine the association between red/processed meat consumption and glycaemic conditions (i.e., prediabetes [preDM] and DM) among middle-aged residents in rural Khánh Hòa, Vietnam. Design: In this cross-sectional study, a multinomial regression model was used to examine the association between daily consumption of red/processed meat (0-99 g, 100-199 g, or ≥ 200 g) and preDM/DM with adjustments for sociodemographic, lifestyle-related, and health-related variables. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…The associations between individual food or nutrient intake and prediabetes have been evaluated previously. Studies have discovered that red meat and TSFAT are positively correlated with the risk of prediabetes [37,38], which is consistent with our results. Our study observed, for the first time, a positive correlation between sodium intake and the risk of prediabetes.…”
Section: Discussionsupporting
confidence: 93%
“…The associations between individual food or nutrient intake and prediabetes have been evaluated previously. Studies have discovered that red meat and TSFAT are positively correlated with the risk of prediabetes [37,38], which is consistent with our results. Our study observed, for the first time, a positive correlation between sodium intake and the risk of prediabetes.…”
Section: Discussionsupporting
confidence: 93%
“…In total, 2942 samples were analyzed. Detailed information on this survey is available in previous studies by Inoue et al (Inoue et al, 2022) and Nguyen et al (Nguyen et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…The baseline survey of the KHCS was conducted between June 2019 and 2020. The detailed information of the survey is available in our previous studies by Inoue et al [20] and Chau et al [21].…”
Section: Study Design and Participantsmentioning
confidence: 99%